Changes in the Jugular Bulb Associated With Sacrifice of the Internal Jugular Vein. Issue 1 (January 2015) - Brook, Christopher D.; Buch, Karen; Gadaleta, Dominick; Jalisi, Scharukh; Grillone, Gregory; Sakai, Osamu; Aliphas, Avner
<x xml:space="preserve">Abstract</x> Objective To determine whether sacrifice of the internal jugular vein (IJV) causes subsequent changes in the jugular bulb. Study Design Retrospective chart review. Setting Tertiary referral center. Patients Patients were selected by CPT code for neck dissection and were included in the study if they had undergone unilateral neck dissection and had preoperative and postoperative computed tomographic scans through the temporal bone. Interventions The jugular bulb was measured in the axial plane for anteroposterior and mediolateral diameters. Main Outcome Measures Cross-sectional area of the jugular bulb was calculated, and comparison was made between preoperative and postoperative studies in patients with or without ligation of the IJV. Results After unilateral neck dissection, the mean change in the size of the jugular bulb ipsilateral to surgery with sacrifice of the IJV was found to be −10.4 mm2 (95% confidence interval [95% CI], ±8.54 mm2); ipsilateral to surgery without sacrifice of the internal jugular, −0.2 mm2 (95% CI, ±3.24 mm2); contralateral to surgery with sacrifice of the IJV, +1.9 mm2 (95% CI, ±11.12 mm2); and contralateral to surgery without sacrifice of the IJVa, +1.0 mm2 (95% CI, ±2.66 mm2). Analysis of variance demonstrated a significant difference for changes in the jugular bulb area ipsilateral to surgery with sacrifice of the IJV (p = 0.03) when compared with contralateral to surgery without sacrifice of the IJV. Conclusion Changes in size of the jugular bulb occur with surgical manipulation of the jugular vein. This study demonstrates a decrease in the size of the jugular bulb with ipsilateral IJV sacrifice.